Aldolase-regulated G3BP1/2+ condensates control insulin mRNA storage in beta cells - Quezada, Esteban; Knoch, Klaus-Peter; Vasiljevic, Jovana; Seiler, Annika; Pal, Akshaye; Gunasekaran, Abishek; Münster, Carla; Friedland, Daniela; Schöniger, Eyke; Sönmez, Anke; Roch, Pascal; Wegbrod, Carolin; et al. (The EMBO journal, 2025)
Upregulation of insulin mRNA translation upon hyperglycemia in pancreatic islet β-cells involves several RNA-binding proteins. Here, we found that G3BP1, a stress granule marker downregulated in islets of subjects with type 2 diabetes, binds to insulin mRNA in glucose concentration-dependent manner. We show in mouse insulinoma MIN6-K8 cells exposed to fasting glucose levels that G3BP1 and its paralog G3BP2 colocalize to cytosolic condensates with eIF3b, phospho-AMPKα Thr172 and Ins1/2 mRNA. Glucose stimulation dissolves G3BP1 + /2 + condensates with cytosolic redistribution of their components. The aldolase inhibitor aldometanib prevents the glucose- and pyruvate-induced dissolution of G3BP1 + /2 + condensates, increases phospho-AMPKα Thr172 levels and reduces those of phospho-mTOR Ser2448 . G3BP1 or G3BP2 depletion precludes condensate assembly. KO of G3BP1 decreases Ins1/2 mRNA abundance and translation as well as proinsulin levels, and impaires glucose-stimulated insulin secretion. Further, other insulin secretagogues such as exendin-4 and palmitate, but not high KCl, prompts the dissolution of G3BP1 + /2 + condensates. G3BP1 + /2 + /Ins mRNA + condensates are also found in primary mouse and human β-cells. Hence, G3BP1 + /2 + condensates represent a conserved glycolysis/aldolase-regulated compartment for the physiological storage and protection of insulin mRNA in resting β-cells. Synopsis How pancreatic islet β-cells regulate insulin production in response to altered blood glucose levels remains ill-defined. Here, the stress granule proteins G3BP1 and G3BP2 are shown to colocalise with insulin mRNA in cytosolic condensates regulating insulin mRNA translation. Glycolysis regulates the dynamic assembly of G3BP1 + /2 + /insulin mRNA + condensates through an aldolase-AMPKα-G3BP1/2 axis. Pancreatic β-cells store insulin mRNA in G3BP1 + /2 + condensates in glucose concentration-dependent manner, enabling glucose-dependent translocation of insulin mRNA to the ER for translation. Depletion of G3BP1, but not of G3BP2, impairs insulin mRNA stability. phospho-AMPKα Thr172 localizes to G3BP1 + /2 + condensates in β-cells exposed to low glucose levels. Inhibition of the glycolytic enzyme aldolase prevents glucose-induced elevation of ATP levels, increasing the phospho-AMPKα Thr172 /phospho-mTOR Ser2448 ratio and the resolution of G3BP1 + /2 + condensates. Insulin secretagogues exendin 4 and palmitate mimic high glucose in resolving G3BP1 + /2 + /insulin mRNA + condensates. Insulin mRNA is translationally repressed in resting β-cells and stored in G3BP granules, which dissolve upon glucose stimulation.